Cloning of the Gene Encoding a Novel Thermostable α-Galactosidase from Thermus brockianus ITI360 - Fridjonsson, Olafur (American Society for Microbiology, 1999)
An α-galactosidase gene from Thermus brockianus ITI360 was cloned, sequenced, and expressed in Escherichia coli, and the recombinant protein was purified. The gene, designated agaT, codes for a 476-residue polypeptide with a calculated molecular mass of 53,810 Da. The native structure of the recombinant enzyme (AgaT) was estimated to be a tetramer. AgaT displays amino acid sequence similarity to the α-galactosidases of Thermotoga neapolitana and Thermotoga maritima and a low-level sequence similarity to α-galactosidases of family 36 in the classification of glycosyl hydrolases. The enzyme is thermostable, with a temperature optimum of activity at 93°C with para-nitrophenyl-α-galactopyranoside as a substrate. Half-lives of inactivation at 92 and 80°C are 100 min and 17 h, respectively. The pH optimum is between 5.5 and 6.5. The enzyme displayed high affinity for oligomeric substrates. The K(m)s for melibiose and raffinose at 80°C were determined as 4.1 and 11.0 mM, respectively. The α-galactosidase gene in T. brockianus ITI360 was inactivated by integrational mutagenesis. Consequently, no α-galactosidase activity was detectable in crude extracts of the mutant strain, and it was unable to use melibiose or raffinose as a single carbohydrate source.